Cellulosmicrobium cellulans isolated from a patient with acute renal failure. Issue 2 (June 2014) - Delport, Johan; Wakabayashi, Adrienne Tamiko; Anantha, Ram Venkatesh; Lannigan, Robert; John, Michael; McCormick, John K.
Abstract : Introduction: Cellulosimicrobium cellulans  is a rare human pathogen that is associated with chronic immunosuppression, such as human immunodeficiency virus infection, post‐transplantation or end‐stage renal disease. Case presentation: A 59‐year old man with a past medical history of significant cardiovascular, cerebrovascular and peripheral vascular disease was admitted to the intensive care unit (ICU) with intractable seizures. Physical examination, radiographic imaging and culture results suggested the patient had developed metabolic encephalopathy due to pneumonia caused by Staphylococcus aureus and Moraxella catarrhalis . The patient recovered neurologically with the use of broad‐spectrum antibiotics but developed acute renal failure during his stay. Seven days later, he relapsed into seizure activity and two separate blood cultures grew Cellulosimicrobium cellulans . Despite maximal antibiotic therapy, the patient continued to deteriorate. After 16 days, the patient's family withdrew care and he subsequently died. Conclusion: We report the isolation of Cellulosimicrobium cellulans from a patient who developed acute renal failure following a prolonged stay in the ICU for sepsis encephalopathy.